New results on two well-studied glaciers of the Pamir - A. A. Yablokov (Lëd i Sneg, 2015)
In summer 2011, after many years of recession, a group of workers from the Hydrographic expeditionary department of the State Hydrometeorological Survey of the Republic Tajikistan visited the Medvezhiy Glacier (at the source of the Vanch River) and the Skogach Glacier (basin of the Obihingo River). Medvezhiy Glacier is a surging one and during this visit it was in its active stage. Its length in comparison with 2005 increased by 800–1000 m, but there was no dam at the Abdukagor River and a dam lake which produces mudflow, as it happened in 1960–70s did not created. At nowadays, the Medvezhiy Glacier advanced a bit further than in time of its previous surge in 2001–2002. The topographic survey of the Skogach Glacier was not performed for twenty years. This glacier retreated and degraded in the last century, but in contrary, it was found that the glacier did not retreat, and its tongue is at the same place where it was in 1991.